DEVELOPMENT OF SCIENCE-LITERACY BASED POCKET BOOK ON GLOBAL WARMING MATERIALS FOR JUNIOR HIGH SCHOOL STUDENTS - Sezy Silviya Ningsih; Andi Suhardi (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
This study aims to describe the validity and responses of students to the development of a science literacy-based pocket book on global warming material for seventh grade of junior high school students. This research is a type of Research and Development which refers to the 4-D Thiagarajan model (Define, Design, Develop and Disseminate). The data collection instrument used a validation questionnaire conducted by the validators (materials, media and users) and a student response questionnaire through two stages, namely a small- scale response test and a large-scale response test. Based on the results of validation by material validators, media validators and users (teachers) were declared very valid with an average percentage of the three validators of 92.12%. The results of the responses of small-scale students were 96.45%. The large scale of 88.24% showed that the responses of students were very interesting to the development of a science literacy-based pocket book on global warming materials for junior high school students.